Current state of chronic wound care in Kazakhstan: focus on topical treatments - Mikhalovsky, S. V.; Akhmetova, Alma; Saliev, Timur; Kulsharova, Gulsim; Nurgozhin, Talgat (Science and Innovations, 2015)
Background — The presence of chronic hard-to-heal wounds significantly affects patients’ quality of life causing pain, discomfort, decrease of mobility and consequently leads to social isolation and depression. This type of wound is more prevalent among older population. It has been estimated that up to 1-2% of the world population have this condition. The treatment of hard-to-heal wounds is expensive and long-term process, and, stresses healthcare systems of every country. Unfortunately, limited information is available about the situation with chronic wounds in Kazakhstan as the statistical data on such patients is not monitored and not registered in this country. Methods — The search was conducted by using available electronic sources, including Google Scholar, PubMed, Web of Sciences, Medline, Wiley Online Library, and Cochrane Library databases as well as hard copy versions of peer-reviewed publications in Russian, Kazakh, and English languages. Results — We have identified and analyzed current situation with wound care in the Republic of Kazakhstan. Research has demonstrated a variety of types of treatments utilized in the country, particularly the treatment of the diabetic foot.It also indicates the lack of statistics on wound care. Conclusions — The review highlights the mechanisms of wound healing process, methods for wound care, and encompasses the information available on wound healing in Republic of Kazakhstan. The article emphasizes the necessity of establishing the systemic monitoring of wound care and formation of electronic database. Apart from that, the importance of developing and manufacturing of domestic novel wound treatments have been also stressed out.
Keywords: Chronic wound; Treatment; Wound dressing